2019
DOI: 10.1530/eje-19-0156
|View full text |Cite
|
Sign up to set email alerts
|

Effects of 6-month vitamin D supplementation on insulin sensitivity and secretion: a randomised, placebo-controlled trial

Abstract: Objective To determine whether vitamin D3 supplementation improves insulin sensitivity, using the hyperinsulinemic-euglycemic clamp. Design This single-centre, double-blind, placebo-controlled trial randomised 96 participants at high risk of diabetes or with newly diagnosed type 2 diabetes to vitamin D3 5000 IU daily or placebo for 6 months. Methods We assessed at baseline and 6 months: (1) primary aim: peripheral insulin sensitivity (M-value using a 2-h hyperinsulinemic-euglycemic clamp); (2) secondary ai… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
59
0
1

Year Published

2020
2020
2022
2022

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 79 publications
(61 citation statements)
references
References 41 publications
(49 reference statements)
1
59
0
1
Order By: Relevance
“…They also demonstrated that administration of 1,25(OH) 2 D into the brain dramatically decreased the food intake and body weight in obese rodents. Although a clear cause and effect for vitamin D in glucose and insulin metabolism and body weight has been established, it is surprising that studies on vitamin D supplementation and CVD have yielded inconsistent results [41][42][43][44][45][46][47].…”
Section: Discussionmentioning
confidence: 99%
“…They also demonstrated that administration of 1,25(OH) 2 D into the brain dramatically decreased the food intake and body weight in obese rodents. Although a clear cause and effect for vitamin D in glucose and insulin metabolism and body weight has been established, it is surprising that studies on vitamin D supplementation and CVD have yielded inconsistent results [41][42][43][44][45][46][47].…”
Section: Discussionmentioning
confidence: 99%
“…by Lemieux et al found that, in subjects at high risk of diabetes or with newly diagnosed T2DM who received 5000 IU vitamin D3 daily for 6 months, peripheral insulin sensitivity and β-cell function increased significantly, suggesting that supplementation with vitamin D3 may slow metabolic deterioration in this population. 21 Previous studies have explored the relationship between vitamin D and blood glucose levels. One study performed in adolescents (aged 12-17 years) in the United States found that vitamin D levels were negatively correlated with fasting blood glucose levels, but were not related to HbA1c in male subjects.…”
Section: Discussionmentioning
confidence: 99%
“…In humans, mechanistic studies show inconsistent results. Vitamin D supplementation for participants at high risk for or with newly diagnosed type 2 diabetes has shown an effect ( 27 ) as well as no effect ( 28 ) on insulin sensitivity and secretion. However, such studies are inconclusive because they are underpowered; have included populations with sufficient vitamin D status, with a low risk for diabetes or with established diabetes; have co-administered vitamin D with other interventions, which may confound the effect of vitamin D; or have followed participants for short periods of time (about 2–6 months), which are likely inadequate to affect the pathophysiology of type 2 diabetes.…”
Section: Review Strategy and Literature Searchmentioning
confidence: 99%